Brain‐derived neurotrophic factor is expressed in rat and human placenta and its serum levels are similarly regulated throughout pregnancy in both species. (17th January 2014) - Garcés, María F.; Sanchez, Elizabeth; Torres‐Sierra, Alejandra L.; Ruíz‐Parra, Ariel I.; Angel‐Müller, Edith; Alzate, Juan P.; Sánchez, Ángel Y.; Gomez, Martín A.; Romero, Ximena C.; Castañeda, Zoila E.; Sanchez‐Rebordelo, Estrella; Diéguez, Carlos; et al.
Summary Objective Pregnancy is characterized by several metabolic changes that promote fat gain and later onset of insulin resistance. As Brain‐derived neurotrophic factor (BDNF) decreases hyperglycaemia and hyperphagia, we aimed to investigate the potential role of placental and circulating BDNF levels in these pregnancy‐related metabolic changes in rats and humans. Design and methods We identified the mRNA and protein expression of placental BDNF and its receptor TrkB using real‐time PCR, Western blot and immunohistochemical approaches in both rat and humans. Serum BDNF was measured by ELISA. We also did a longitudinal prospective cohort study in 42 pregnant women to assess BDNF levels and correlations with other metabolic parameters. Results We found that BDNF and TrkB are expressed in both rat and human placenta. In rat, both placental mRNA and serum levels are increased throughout pregnancy, whereas their protein levels are significantly decreased at the end of gestation. Serum BDNF levels in pregnant women are significantly lower in the first trimester when compared to the second and third trimester (P < 0·0148, P < 0·0012, respectively). Serum BDNF levels were negatively correlated with gestational age at birth and fasting glucose levels. Conclusion Our findings suggest that both BDNF and its receptor TrkB are expressed in rodent and human placenta being regulated during pregnancy. Taken together, these findings support a role of BDNF in the regulation of several metabolic functions during pregnancy.